2014
DOI: 10.1128/jcm.02381-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotype Distribution of Pneumocystis jirovecii in Cuban Infants and Toddlers with Whooping Cough

Abstract: e This study describes the prevalence and genotype distribution of Pneumocystis jirovecii obtained from nasopharyngeal (NP) swabs from immunocompetent Cuban infants and toddlers with whooping cough (WC). A total of 163 NP swabs from 163 young Cuban children with WC who were admitted to the respiratory care units at two pediatric centers were studied. The prevalence of the organism was determined by a quantitative PCR (qPCR) assay targeting the P. jirovecii mitochondrial large subunit (mtLSU) rRNA gene. Genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
2
12
0
6
Order By: Relevance
“…Other potential disadvantages include challenges in interpretation of band patterns with minor differences and in data exchangeability between different laboratories. RFLP has been used most extensively to detect mutations in the dhps gene of P. jirovecii (346)(347)(348)(349)(350)(351)(352)(353)(354). Recently, RFLP was adapted to identify polymorphisms of the P. jirovecii msg repertoire (355-357); we refer to this method as msg-RFLP henceforth.…”
Section: Epidemiology Of Pneumocystis Methods For Molecular Typingmentioning
confidence: 99%
“…Other potential disadvantages include challenges in interpretation of band patterns with minor differences and in data exchangeability between different laboratories. RFLP has been used most extensively to detect mutations in the dhps gene of P. jirovecii (346)(347)(348)(349)(350)(351)(352)(353)(354). Recently, RFLP was adapted to identify polymorphisms of the P. jirovecii msg repertoire (355-357); we refer to this method as msg-RFLP henceforth.…”
Section: Epidemiology Of Pneumocystis Methods For Molecular Typingmentioning
confidence: 99%
“…The very low number of samples in which Pneumocystis colonization was detected limits comparison with other studies. However, it should be noted that genotype 2 was also found to be predominant in Italy (39%) [18] and in Cuba (48%) [19] . Nevertheless, our results contrasted with a Spanish study that reported a predominance of genotype 1 in patients with pulmonary diseases (45%) [11] .…”
mentioning
confidence: 95%
“…Thus, alternative molecular tools (9, 10), such as multilocus sequence typing (MLST), microsatellite genotyping, or PCR-restriction fragment length polymorphism (PCR-RFLP) analysis, have been used to trace strain circulation in the context of hospitals (11)(12)(13). Microsatellite genotyping may be more appropriate for detection of mixed infections (14), and PCR-RFLP analysis of the mitochondrial large-subunit rRNA gene (mtLSU) alone has appeared to be sufficient for roughly distinguishing between strains (12, 13), but MLST has been shown to be highly reproducible and facilitates comparison of data from different laboratories (11).…”
mentioning
confidence: 99%